2023
DOI: 10.26434/chemrxiv-2023-b8nnx
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Precise control over gas transporting channels in zeolitic imidazolate framework glasses

Abstract: Porous materials, such as metal-organic frameworks emerge to solve important quests of our modern society, such as CO2 sequestration. Zeolitic Imidazolate Frameworks (ZIFs) can undergo a glass transition to form ZIF-glasses; they combine the liquid handling of classical glasses with tremendous potential for gas separations. Using millimeter-sized ZIF-62 single crystals and centimeter-sized ZIF-62-glass we demonstrate scalability and processability. Further, following the evolution of gas penetration into ZIF-c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
41
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(43 citation statements)
references
References 39 publications
2
41
0
Order By: Relevance
“…30−33 The porosity features of MOF glasses and the associated functions can be tuned by variations in the type of organic linkers and thermal processing methods. 34,35 Furthermore, the dense and disordered nature of MOF glasses results in improved proton/ thermal conductivity functionalities of the crystalline phase. 36,37 Thus, some advantages of the MOF glasses in terms of their functionality can be attributed to the intrinsic dynamic motion at the molecular level and the associated transport properties of mass, ions, and photons.…”
Section: ■ Introductionmentioning
confidence: 99%
“…30−33 The porosity features of MOF glasses and the associated functions can be tuned by variations in the type of organic linkers and thermal processing methods. 34,35 Furthermore, the dense and disordered nature of MOF glasses results in improved proton/ thermal conductivity functionalities of the crystalline phase. 36,37 Thus, some advantages of the MOF glasses in terms of their functionality can be attributed to the intrinsic dynamic motion at the molecular level and the associated transport properties of mass, ions, and photons.…”
Section: ■ Introductionmentioning
confidence: 99%
“…5–8 They show promising functions including selective gas permeability, ion transport, protection, and optical switching. 9–16…”
mentioning
confidence: 99%
“…[5][6][7][8] They show promising functions including selective gas permeability, ion transport, protection, and optical switching. [9][10][11][12][13][14][15][16] Since several Zn 2+ -azolate-based frameworks were found to form glassy states by melt-quenching, the library of CP/MOF glasses is expanding with more available ligands. 17 One of the ligand systems that is not able to construct CP/MOF glasses to date is dicarboxylates.…”
mentioning
confidence: 99%
“…Metal–organic frameworks (MOFs) are composed of inorganic and organic building units, which interconnect to form crystalline porous coordination networks. , They have numerous potential uses within, e.g., gas storage and separation, , catalysis, and drug delivery . Typically, these crystalline compounds decompose irreversibly at elevated temperatures (200–600 °C), but it has recently been shown that some MOFs can undergo melting before thermal decomposition. , In turn, this enables quenching of the molten MOF phase to a glassy state .…”
mentioning
confidence: 99%
“…For example, this is the case for the well-studied ZIF-4 (Zn­(Im) 2 , where Im is imidazolate), which exhibits no significant N 2 uptake and reduced CO 2 uptake in its glassy state compared to the corresponding crystal phase. , Pore collapse is, however, not a given in MOF glasses. For example, the degree of pore collapse in ZIF-62 (ZnIm 1.75 bIm 0.25 , where bIm is benzimidazolate) depends on the processing conditions, and partial retention of porosity after melt quenching has been observed in some other ZIF systems, including Co-ZIF-62, ZIF-76-ClbIm (Zn­(Im) 1.62 (ClbIm) 0.38 , where ClbIm is chloro­benzimidazolate), and ZIF-76-mbIm (Zn­(Im) 1.33 (mbIm) 0.67 , where mbIm is methyl­benzimidazolate) glasses . In the two ZIF-76-based glasses, MRO in the crystal state was partially preserved in the glass phase as observed from retention of features above 6 Å in the experimentally measured pair distribution functions .…”
mentioning
confidence: 99%